2009
DOI: 10.1007/s11249-009-9445-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dwell Time on the Static Friction in Creeping Elastic–Plastic Polymer Spherical Contact

Abstract: A theoretical model is developed to study the effect of dwell time on the junction growth and static friction of a creeping polymer sphere in contact with a rigid flat under full stick contact condition. A rapid normal loading into the elastic-plastic contact regime is followed by a rest period during which creep takes place causing contact area growth, and stress relaxation that can completely eliminate the plastic zone in the sphere. At the end of this rest time, an increasing tangential loading is applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Many authors220233738 have reported that that the static friction coefficient of rubber depends on the initial dwell time and the rate of starting, which is definitively consistent with our results. Here, this effect is even stronger under lubricated conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many authors220233738 have reported that that the static friction coefficient of rubber depends on the initial dwell time and the rate of starting, which is definitively consistent with our results. Here, this effect is even stronger under lubricated conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The μ s is known to be sensitive to the dwell time before the actual movement2021222324, which is very likely from the increasing real contact area as a function of the contact time. The effect of the dwell time on the static friction was studied in the linear friction tester by loading the rubber sample against a dry or wet glass surface with a force of 400 N for different dwell times ranging from 2 to 600 s. Figure 4 confirms that the dwell time substantially influenced the static friction force on dry glass.…”
Section: Resultsmentioning
confidence: 99%
“…Differences are possibly due to a larger area of interaction that is expected with the greater surface conformity of softer gels. Similar observation reported for the effect of dwell time in creeping elastic-plastic polymers (Malamut et al, 2009) and articular cartilages that was reinforced with tissueinterpenetrating polymers (Cooper et al, 2017). COF values of hard gels, more like a solid base body, stayed at a constant friction level, in contrast to soft gels, for which a slight steady increase was observed during the duration of the tribological tests.…”
Section: Surface Chemistry Determination X-ray Photoelectron Spectroscopysupporting
confidence: 81%
“…Based on this analysis, they also found that the residence time had an obvious effect on interface properties, but the relationship between residence time and friction was ignored. Malamut [21] and Kasem [22] presented experimental research on the time effect of static friction forces on spherical polymers, and they found that the time effect of the static friction force is related to the creep of materials; they proposed a theoretical creep model.…”
Section: Introductionmentioning
confidence: 99%